2017
DOI: 10.11646/phytotaxa.317.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Argostemma cordatum (Rubiaceae), a new species from Vietnam

Abstract: Argostemma cordatum, a new species of Rubiaceae, is described and illustrated. The species was discovered in 2014 during a botanical survey of the Chu Yang Sin National Park (Dak Lak province, Southern Vietnam). Argostemma cordatum possesses a solitary large leaf per plant (along with one very small leaf). The new species differs from morphologically similar species mainly by the small size of the enlarged leaf and cordate base of the enlarged leaf. It is also characterized by the following features: plant com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Detailed examination of the specimens and studies on the protologues and type specimens of previously known species revealed that the morphological characters of these specimens match with those of Argostemma pictum Wall. -a species distributed mainly in Myanmar, Thailand, Peninsular Malaysia, and Laos (Sridith, 2007;Lanorsavanh & Chantaranothai, 2019), however, this species has not yet been reported for Vietnam in previous treatments (Pitard, 1923;Pham, 2003;Choudhary et al, 2013;Govaerts et al, 2017;Nuraliev et al, 2017;Quang et al, 2019;Do et al, 2020). Therefore, we report here A. pictum as a new record for the flora of Vietnam bringing the number of species in the genus to 10, of which, six species, i.e.…”
Section: Notes On Taxonomy Of the Genus Argostemma (Rubiaceae) From Vmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed examination of the specimens and studies on the protologues and type specimens of previously known species revealed that the morphological characters of these specimens match with those of Argostemma pictum Wall. -a species distributed mainly in Myanmar, Thailand, Peninsular Malaysia, and Laos (Sridith, 2007;Lanorsavanh & Chantaranothai, 2019), however, this species has not yet been reported for Vietnam in previous treatments (Pitard, 1923;Pham, 2003;Choudhary et al, 2013;Govaerts et al, 2017;Nuraliev et al, 2017;Quang et al, 2019;Do et al, 2020). Therefore, we report here A. pictum as a new record for the flora of Vietnam bringing the number of species in the genus to 10, of which, six species, i.e.…”
Section: Notes On Taxonomy Of the Genus Argostemma (Rubiaceae) From Vmentioning
confidence: 99%
“…Although several taxonomic treatments of the genus were published for geographical areas, e.g. the Malay peninsula and peninsular Thailand (Ridley, 1923;Sridith, 1999Sridith, , 2007Sridith & Puff, 2000), Laos (Lanorsavanh & Chantaranothai, 2013, 2019, China (Chen et al, 2011), and Vietnam (Pitard, 1923;Pham, 2003), a worldwide monographic study has not yet been attempted. The Malay Peninsula, Peninsular Thailand and Borneo were considered as centres of diversity of Argostemma; 31 species were recorded for the flora of Thailand (Sridith, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…86 genera and 510 species (Pitard, 1922;Ho, 2003;Tran, 2005). Of late, several new species belonging to Rubiaceae have been described from Vietnam including four species of Argostemma (Choudhary et al, 2013;Nuraliev et al, 2017;Bui et al, 2019;, two species of Leptomischus (Wu et al, 2020;Tran et al, 2021a), 15 new species of genus Lasianthus (Dang et al, 2022) along with several new records. The Rubiaceae are highly diverse in Indo-China, however, the taxonomic inventories of Rubiaceae in the regional flora remain incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…A dozen of new species have been added to the genus from S.E. Asia over the last 10 years (Sridith 2012;Choudhary et al 2013;Lanorsavanh and Chantaranothai 2016;Nuraliev et al 2017;Quang et al 2019;Hsu et al 2020;Lanorsavanh et al 2020;Van Do et al 2020).…”
Section: Introductionmentioning
confidence: 99%